Can discuss bullying in nursing? - Ellen Hagopian Ellen; Genvial Freitas Genival; Kleber Costa Kleber (Universidad de Alicante, 2016)
Bullying is an unethical conduct that disrupts the balance in the workplace and appears contrary to morals and good faith that should guide social and labor relations (Alkmim, 2005). Objective: Identify and analyze the scientific literature on the phenomenon of bullying in nursing. Method: Systematic literature review with qualitative approach. Inclusion criteria: all categories of articles with full text; published in Portuguese, English or Spanish between 2005 and 2014 and articles interconnect issues about bullying, sexual harassment and nursing. Results: Among the established criteria were selected twelve articles. It was found that bullying manifests itself in different ways, in concrete situations experienced by nursing staff and grouped by similarity into categories that depict the perceptions and consequences of the phenomenon as well as the actions taken for solving them. Conclusion: We conclude that the discussion of the phenomenon in nursing should be expanded to better understanding and coping with bullying in this category with the expectation that the phenomenon is no longer silent, hidden and pass to be discussed openly influencing the process improvement of the nursing work.